Adaptation of local work organization to modern conditions - D. Yu. Levin (Вестник Научно-исследовательского института железнодорожного транспорта)
The current state of the organization of local work is characterized by a large number of normative and technological documents that are developed without mutual coordination. Therefore, often the actual situation and the volume of the local work are significantly different from the normative conditions. Disadvantages of the existing organization of local work are: - performance planning of local work based on the achieved performance level of technical tasks cumulative from the beginning of the month without taking into account the real capabilities of stations and freight fronts; - criteria for shunting work does not take into account the use of loading and unloading capabilities of freight fronts; - evaluation of the effectiveness of local work organization does not take into account the final results of freight operations. The end result of local work should be the maximum volume of loading and unloading. The criterion for organizing local work is the optimal working conditions for freight fronts, when, by the time the freight operations are completed, the station has cars for the next timely delivery. The task of operational planning for local work in a mathematical formulation is formulated in terms of the distribution of flows on graphs. The developed algorithm for performing calculations leads to ranging the flow of car arrival to the station to ensure the maximum possible amount of freight work, and also determines the required schedule for its arrival. An operational plan for the transportation of local cars to stations and its supply to freight fronts is being developed as a result of automation of operational planning of local and freight work.